2003
DOI: 10.1097/00129689-200308000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison Between Different Insufflation Pressures for Laparoscopic Cholecystectomy

Abstract: Laparoscopy using carbon dioxide insufflation induces adverse effects in both the cardiovascular and the respiratory function. The use of low pressure pneumoperitoneum has been shown to reduce adverse hemodynamic effects. However, its effect on tissue trauma and postoperative pain and recovery remains controversial. The aim of this study was to compare tissue trauma, postoperative pain, and recovery in two groups of patients undergoing laparoscopic cholecystectomy, one at insufflation pressure of 8 (LC8) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
2
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 15 publications
2
50
2
5
Order By: Relevance
“…Some studies have also shown that the shoulder tip pain is minimal if the initial insufflation rate is kept suboptimal, although this needs to be substantiated. Some studies have shown that the incidence and intensity of postoperative shoulder tip pain was significantly less in the low-pressure pneumoperitoneum group when compared with standard-pressure pneumoperitoneum groups [8,[11][12][13][14][15][16]. Our study, however, shows that the incidence of shoulder pain has no statistical difference between groups undergoing laparoscopic surgery at different pneumoperitoneal pressures.…”
Section: Discussioncontrasting
confidence: 71%
“…Some studies have also shown that the shoulder tip pain is minimal if the initial insufflation rate is kept suboptimal, although this needs to be substantiated. Some studies have shown that the incidence and intensity of postoperative shoulder tip pain was significantly less in the low-pressure pneumoperitoneum group when compared with standard-pressure pneumoperitoneum groups [8,[11][12][13][14][15][16]. Our study, however, shows that the incidence of shoulder pain has no statistical difference between groups undergoing laparoscopic surgery at different pneumoperitoneal pressures.…”
Section: Discussioncontrasting
confidence: 71%
“…The effect is maintained for 3-5 postoperative days, thus contributing to an improved QOL for these patients, chiefly in the physical domain [2,3,14,19,20]. Yet not all investigators are uniformly positive in their assessment of LP [13]. Most likely, the differences become statistically significant only in trials involving larger groups of patients [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…15 However Celik et al and Perrakis et al have shown that the pressure levels did not affect pain scores. 16,17 Wallace et al compared 7.5 and 15mmHg pressure and reported less pain in the LPG. 18 Vilos et al, the intraperitoneal pressure was correlated positively with BMI and weight and negatively with parity.…”
Section: Discussionmentioning
confidence: 99%